(untitled) (Tanzania Medical Journal, 2022)
Background In the past few years, there has been a rising interest in alternative therapies and the usage of herbal products in the treatment of peptic ulcer disease. Tumbo Mixture® is amongst medicinal plant used in Tanzania in the management of the gastric ulcers, however, to date scant information is available on effectiveness of treatment of gastric ulcers. Our study intended to investigate possible histological changes in the stomach of ulcerated rats fed with Tumbo Mixture® so as to confirm the claim by traditional healer that this blended product has anti-ulcer effects. Broad objective The aim of the study was to evaluate the histological changes on ethanol-induced acute gastric ulcers in rats fed with Tumbo Mixture®. Methods Completely randomized block design conducted at MUHAS, Tanzania. Experiment involved 20 Wister rats weighing 200 - 250g, age range of 9-12 weeks. Animals were divided equally into NCG: given only normal saline and served to compare a normal gastric mucosa with that of an ulcerated one, UCG: given only ethanol without treatment, PTG and UTG. Ethanol was administrated to UCG and UTG orally through gastric gavages (2.5mls/kg) to induce gastric ulcers. Tumbo Mixture® (45 ml/kg) was given three times daily for 14 days. At the end of treatment animals were euthanized, stomachs opened and washed, photographed, fixed with 10% neutral buffered formalin, stained with H&E and evaluated for gastric changes. Materials used: Tumbo mixture, Wistar rats, absolute ethanol, digital camera, digital microscope, formaldehyde, ethanol, xylene, potassium alum, mercuric oxide, sodium phosphate monobasic and sodium phosphate dibasic. Results Gastric mucosa of ethanol-induced gastric ulcers rats fed with Tumbo Mixture® showed different histological changes including; decreasing in gastric lesions, focal dilated blood vessels, mild oedema and limited inflammatory cells infiltration. Those results signified that Tumbo Mixture contributes in alternative treatment of peptic ulcers. In the pre-treated group normal mucosa was shown with new formation of uniform blood vessels. Conclusion and recommendation Tumbo Mixture® was effective on the treatment of an ethanol-induced acute gastric ulcers as demonstrated by cell proliferation, secretary and ant-inflammatory effect which lead to repairing of ethanol-induced gastric damages. Further research aiming at cellular mechanisms for this product is recommended.